Generador automático de código PLC para programas especificados gráficamente con una representación GEMMA-GRAFCET (2021)
A PLC code generator for graphically specified programs is presented. The graphic specification follows the GEMMA-GRAFCET representation and is peformed through the tool. The model-driven engineering methodology is used to guide development. The tool was validated with a case study to identify opportunities for improvement and verify the functionalities.